The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/1463-1741.144418
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure immediately activates cochlear mitogen-activated protein kinase signaling

Abstract: Noise-induced hearing loss (NIHL) is a major public health issue worldwide. Uncovering the early molecular events associated with NIHL would reveal mechanisms leading to the hearing loss. Our aim is to investigate the immediate molecular responses after different levels of noise exposure and identify the common and distinct pathways that mediate NIHL. Previous work showed mice exposed to 116 decibels sound pressure level (dB SPL) broadband noise for 1 h had greater threshold shifts than the mice exposed to 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…DUSP1 expression is low during development in almost all tissues except liver and intestine. RNAseq studies indicate that it is expressed in the cochlea and vestibule, particularly in supporting cells (data available from gEAR, umgear.org) (Burns et al, 2015; Elkon et al, 2015; Liu et al, 2014; Scheffer et al, 2015), and that it is upregulated in the cochlea after exposure to noise (Alagramam et al, 2014). In general, MKP family members have been reported to present low basal levels of expression in most tissues (Camps et al, 2000) but they are rapidly induced after stress stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…DUSP1 expression is low during development in almost all tissues except liver and intestine. RNAseq studies indicate that it is expressed in the cochlea and vestibule, particularly in supporting cells (data available from gEAR, umgear.org) (Burns et al, 2015; Elkon et al, 2015; Liu et al, 2014; Scheffer et al, 2015), and that it is upregulated in the cochlea after exposure to noise (Alagramam et al, 2014). In general, MKP family members have been reported to present low basal levels of expression in most tissues (Camps et al, 2000) but they are rapidly induced after stress stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive network and pathway analysis indicated that the MAPK3/MAPK1 MAP kinase serves as one of the crucial nodal molecules in regulating human genetic deafness ( 18 ), highlighting the close association between MAPK signaling pathway and hearing loss. Using a rodent model of noise-induced hearing loss, Alagramam et al ( 19 ) demonstrated that MAPK signaling pathway was activated after noise exposure. MAPK1 , known as ERK2, plays multifactorial roles in mediating cell survival, proliferation, differentiation, and death ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…3034 Specifically, it is hypothesized that cellular stress such as aminoglycoside exposure in the cochlea results in the formation of reactive oxygen species and free radicals that cause the JNK kinase to activate c-Jun. 35 The activated c-Jun transcription factor binds other transcriptional complexes which ultimately results in the complete loss of cochlear hair cells.…”
Section: Discussionmentioning
confidence: 99%